INFLUENCE OF «GREAT CRISIS» EPOCH ON EVERYDAY LIFE OF INTELLIGENTSIA IN THE NORTH CAUCASUS IN 1930s - E. N. Strekalova (Гуманитарные и юридические исследования)
The article studies daily life of provincial intelligentsia in 1930s with the reference to Stavropol and North Caucasus areas. The influence of Stalin epoch of «Great crisis» on daily life of intelligentsia is analyzed. The impact of mobilization economy and repressive policy during the first five-year plans are examined. The reasons for interaction and confrontation of authority and intelligentsia are shown.